Cover Image, Volume 3, Number 6, November 2021. Issue 6 (24th November 2021) - Guo, Yichuan; Khatoon, Rabia; Lu, Jianguo; He, Qinggang; Gao, Xiang; Yang, Xiaopeng; Hu, Xun; Wu, Yang; Lian, Jiale; Li, Zhoupeng; Ye, Zhizhen
Abstract : Front cover image : Lithium‐sulfur batteries (LSBs) are expected to be the next generation energy storage devices. However, LSBs suffer from capacity fading severely due to the "shuttle effect". In article number 10.1002/cey2.145, Jian G. Lu et al. report pollen derived porous carbon/cuprous phosphide (PC/Cu3 P) hybrids to regulate adsorption ability toward polysulfides for LSBs. The PC/Cu3 P LSBs have high specific capacity, high initial coulombic efficiency, and ultra‐long cycling stability, and can work well at high temperatures such as 150°C. The strategy of PC/Cu3 P hybrid proposes new opportunities for ultrastable high‐temperature LSBs.